Características ultra-estruturais das células de Sertoli do morecego hematófago (Desmodus rotundus rotundus, Geoffrey, 1810). - Orsi, A. M.; Vicentini, Carlos Alberto [UNESP]; Dias, S. M.; Vincentini, I. B.; Moreno, M. H. (My University, 1993)
This paper deals with the ultrastructural study of mature vampire bat Sertoli cells and their relationships with the different stages of testicular germ cells. In vampire bat seminiferous epithelium there are different types of junctional specializations among Sertoli cells and among Sertoli cells and different germ cells, with special emphasis to tight junctions and to junctions like as desmosomes. Ectoplasmic junctions through the Sertoli cells, including the smooth ER, are observed. These cellular interactions and their cytophysiological roles are discussed. Also are related some ultrastructural peculiarities of the Sertoli cell nucleus, nucleolus, cytoplasmic organelles and lipidic inclusions.
Ultrastructural characteristics of Sertoli cells of the vampire bat (Desmodus rotundus rotundus, Geoffrey, 1810)
Keywords: animal; bat; electron microscopy; histology; male; seminiferous tubule epithelium; Sertoli cell; ultrastructure; Animal; Chiroptera; English Abstract; Male; Microscopy, Electron; Seminiferous Epithelium; Sertoli Cells; Support, Non-U.S. Gov't